1996
DOI: 10.1007/bf00403918
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of glucose metabolism and insulin secretion during normal pregnancy and pregnancy complicated by gestational diabetes

Abstract: Gestational diabetes affects 2-3% of pregnant women and is associated with foetal complications including macrosomia and an increased likelihood of developing diabetes in later life. We have therefore studied seven women with gestational diabetes and five control women both during the third trimester of pregnancy and again 2-3 months post-partum, using the minimal model analysis of the frequently sampled labelled ([6,6-2H2]-glucose) intravenous glucose tolerance test. Glucose tolerance (glucose Kd) was signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(23 citation statements)
references
References 28 publications
0
23
0
Order By: Relevance
“…Although the pathophysiological mechanisms of GDM have not been fully elucidated, it was well known that the insufficient adaptability of pancreatic β cell to insulin resistance, which is characterized by mid‐late pregnancy, maybe the primary cause of GDM . During normal pregnancy, the stability of glucose in pregnant women depends on the physiological accumulation of insulin secretion; furthermore, this compensatory accumulation is closely related to the biological functions of pancreatic β cells: it is speculated that several regulatory molecules, such as cell growth regulator, which can regulate the biological function of the pancreatic β cell, play a crucial effect in these adaptive changes to meet these compensatory requirements . Therefore, studies about β cells upstream and downstream regulatory factors could make a lot of sense to develop a new treatment target for GDM …”
Section: Introductionmentioning
confidence: 99%
“…Although the pathophysiological mechanisms of GDM have not been fully elucidated, it was well known that the insufficient adaptability of pancreatic β cell to insulin resistance, which is characterized by mid‐late pregnancy, maybe the primary cause of GDM . During normal pregnancy, the stability of glucose in pregnant women depends on the physiological accumulation of insulin secretion; furthermore, this compensatory accumulation is closely related to the biological functions of pancreatic β cells: it is speculated that several regulatory molecules, such as cell growth regulator, which can regulate the biological function of the pancreatic β cell, play a crucial effect in these adaptive changes to meet these compensatory requirements . Therefore, studies about β cells upstream and downstream regulatory factors could make a lot of sense to develop a new treatment target for GDM …”
Section: Introductionmentioning
confidence: 99%
“…2) A physiologic increase in insulin resistance that occurs in all women during the second half of pregnancy and disappears postpartum. Supporting this concept, several studies have shown insulin resistance in women with GDM to be equal or greater than that in nondiabetic pregnant women [20][21][22]. This applies equally to insulin resistance in skeletal muscle and liver and to insulin resistance in the adipose tissue, the latter resulting in increased lipolysis [17,23].…”
Section: Ffas and Insulin Resistance During Gdmmentioning
confidence: 85%
“…A cross-sectional study performed by Buchanan et al [47] in 1990 demonstrated lower insulin sensitivity in women with GDM. However, later studies by Bowes et al [48] and Persson et al [49] contradicted those results and showed that insulin sensitivity was signifi cantly lower during pregnancy than after delivery in patients with GDM. Also, insulin secretion was increased during pregnancy in normal individuals compared with the immediate postpartum period.…”
Section: Gdm and Insulin Resistancementioning
confidence: 93%